Ekspresi Literasi di SDN 1 Mesanggok Dengan Taman Baca Berwarna Serita: Sekolah Ceria Pustaka - Abdul Rasyid; Ayu Junita Aryani; Baiq Farisa Dila; Muhammad Rizqon Zulfanni; Nurkhaerat Alimuddin; Ni Made Yeni Suranti (Indonesian Journal of Education and Community Services, 2025)
The community service program "SERITA: Happy Library School" was carried out at SDN 1 Mesanggok, Lombok, aiming to address challenges in students' literacy. Although awareness of literacy in West Nusa Tenggara continues to grow, obstacles still persist, such as low reading interest, limited reading materials, and unattractive facilities. Through the Student Creativity Program (PKM) of the University of Mataram, the SERITA program introduced a colorful reading corner designed to stimulate students’ interest in reading. The program engaged students, teachers, parents, and the community in creating a sustainable culture of literacy. The results showed an increase in students’ interest in reading, particularly in fiction books, with additional benefits including social interaction and the development of creativity. Ongoing collaboration between schools and the community is recommended for the long-term success of this literacy initiative.